TAZ target gene ITGAV regulates invasion and feeds back positively on YAP and TAZ in liver cancer cells - Weiler, Sofia Maria Elisabeth; Lutz, Teresa; Bissinger, Michaela; Sticht, Carsten; Knaub, Maria; Gretz, Norbert; Schirmacher, Peter; Breuhahn, Kai (Cancer letters, 2020)
The Hippo pathway effectors yes-associated protein (YAP) and WW domain containing transcription regulator 1 (TAZ/WWTR1) support tumor initiation and progression in various cancer entities including hepatocellular carcinoma (HCC). However, to which extent YAP and TAZ contribute to liver tumorigenesis via common and exclusive molecular mechanisms is poorly understood. RNAinterference (RNAi) experiments illustrate that YAP and TAZ individually support HCC cell viability and migration, while for invasion additive effects were observed. Comprehensive expression profiling revealed partly overlapping YAP/TAZ target genes as well as exclusively regulated genes. Integrin-αV (ITGAV) is a novel TAZ-specific target gene, whose overexpression in human HCC patients correlates with poor clinical outcome, TAZ expression in HCCs, and the abundance of YAP/TAZ target genes. Functionally, ITGAV contributes to actin stress fiber assembly, tumor cell migration and invasion. Perturbation of ITGAV diminishes actin fiber formation and nuclear YAP/TAZ protein levels. We describe a novel Hippo downstream mechanism in HCC cells, which is regulated by TAZ and ITGAV and that feedbacks on YAP/TAZ activity. This mechanism may represent a therapeutic target structure since it contributes to signal amplification of oncogenic YAP/TAZ in hepatocarcinogenesis.